EDUKASI PEMANFAATAN PUPUK BIOGAS PADAT DARI SAMPAH ORGANIK UNTUK MENINGKATKAN KOMODITAS PERTANIAN DAN WISATA DESA PERESAK - Isnawati Isnawati; Muh. Azmi Harun; Ergi Putra Febtiawan; Muh. Fauzan Adhiem; Sabrina Faza Salsabila; Nada Fatin Nabila; Dania Fahirani; Desi Ratna Sari; Ahmad Setatriajaya; Nurul A’ini (Universitas Mataram, 2023)
Presak Village, Batu Kliang sub-district, Central Lombok has the potential for sustainable agriculture, farming, and a tourism spot that can be developed, but the people have a middle to lower economic level. This is due to the lack of information regarding the utilization of organic waste as fertilizer by farmers amidst the lack of even distribution of fertilizers, then the lack of utilization of natural resources and tourism management which concerns the interests of the surrounding community. Therefore, the Village Community Empowerment Real Work Lecture (KKN) group is motivated to educate the community in making solid organic fertilizer by utilizing the biogas system to help and be utilized by farmers who can later help reduce the use of chemical fertilizers through several KKN programs, so that they can increase community economy. Using the lecture and mentoring method, specifically the socialization activity for making solid fertilizer (Bokashi) was held on Saturday 29 July 2023. This activity was enthusiastically attended by the participant because there were 1000 fruit seeds distributed. In addition, the material for making biogas fertilizer is considered very beneficial for the community, especially after seeing the difference in the yield of vegetables that are given fertilizer are of higher quality compared to vegetables that are not given fertilizer. For this reason, the program is considered successful, at least there are a lot of people who want to prove the benefits of biogas fertilizer, as evidenced by the enthusiasm of the people who took the seeds provided